PENGARUH VARIASI BEBAN PENDINGIN TERHADAP PRESTASI KERJA MESIN PENDINGIN DENGAN REFRIGERAN R12 DAN LPG - Moch. Rizal A. Y.; Nasrul Ilminnafik; Digdo Listyadi (ROTOR, 2013)
In this research discusses the influence of the cooling load variations on job performance refrigeration includes refrigeration capacity, coefficient of performance and cooling time, the compressor, the impact of refrigeration and compression work with refrigerants R12 and LPG. This study uses a variation of the load is light 20watt, 40Watt, 60Watt, and 80watt at the time of the study for 30 minutes for each of the cooling load, the file retrieval is done use the cooling machine refrigerator sanyo type with dimensions of 90 cm x 45 cm x 45 cm. The results showed the optimum value of COP (coeficient of Performance) of the fridge that I use on the refrigerant R12 and LPG with a load of 40 watts and 30 minutes was 4.75 for R12 and 5.00 for LPG,Obtained that use LPG refrigerant temperature produced less than R12 at the same time that is 30 minutes, the temperature on LPG without cooling load is 10 oC, the load is 11 oC 20 watt, 40 watt load by 12 oC, 60 watt load of 15 oC, and for a load of 80 watts by 17 oC and R12 produced no load temperature is 12 oC, 20 watt load as big as 13 oC, 40 oC as a 15 watt, 60 watt load of 16 oC, and for a load of 80 watts of 18  oC it is seen that the use of LPG refrigerants better because it has a pretty good engine performance compared to R12 views of COP obtained from the same load. Key word: Cooling load ,COP, LPG, refrigerant